Ablation depth control with 40 nm resolution on ITO thin films using a square, flat top beam shaped femtosecond NIR laser. (September 2016) - Kim, Hoon-Young; Yoon, Ji-Wook; Choi, Won-Suk; Kim, Kwang-Ryul; Cho, Sung-Hak
Abstract: We reported on the ablation depth control with a resolution of 40 nm on indium tin oxide (ITO) thin film using a square beam shaped femtosecond (190 fs) laser ( λ p =1030 nm). A slit is used to make the square, flat top beam shaped from the Gaussian spatial profile of the femtosecond laser. An ablation depth of 40 nm was obtained using the single pulse irradiation at a peak intensity of 2.8 TW/cm 2 . The morphologies of the ablated area were characterized using an optical microscope, atomic force microscope (AFM), and energy dispersive X-ray spectroscopy (EDS). Ablations with square and rectangular types with various sizes were demonstrated on ITO thin film using slits with varying x – y axes. The stereo structure of the ablation with the depth resolution of approximately 40 nm was also fabricated successfully using the irradiation of single pulses with different shaped sizes of femtosecond laser. Highlights: ITO thin film was patterned using a femtosecond laser direct patterning technique. The square shaped laser beam with flat-top energy distribution was carried out using a slit module. The square shaped laser beam with pulse number control technique was applied for ablation depth control. The ablation depth control with a resolution of 40 nm on ITO thin films was investigated using a square beam-shaped femtosecond laser. Ablations with square and rectangular types with various sizes were demonstrated on ITO thin film.